The Effects of Experience on Selecting Innovation Projects: Better the Devil You Know - Tobias Schmidt; Franz Schwiebacher; Wolfgang Sofka (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Innovation success depends heavily on firm's ability to set priorities and select the most promising options from its project portfolio before the odds of success or failure become visible and reliable. We ask: What does previous innovation experience tell firms about what not to do in the future? With this in mind, we focus on projects that did not materialise or were abandoned - an important building block for choosing and implementing the 'right' projects. We suggest two major learning mechanisms. On the one hand, real options theory suggests a process based on financial data. On the other hand, research on absorptive capacities finds that previous innovation experience translates into superior ability to value, extract and exploit external knowledge. We test both hypotheses on an empirical basis for more than 600 German firms, covering innovation activities in the period 1997 to 2005. Our results indicate congruence between firms' innovation experience and their project selection patterns. Extensive R&D experience materialises as a stock of knowledge that enables firms to judge projects based on knowledge criteria. Non-R&D innovation experience, stemming from producing and introducing products to markets, resonates as decision-making based on economic factors in the future. Both types of innovation experience appear to generate distinct decision-making capabilities inside the firm which are subsequently exploited in selecting projects for the future.
Keywords: O32; O31; F23; D83; 330; Project selection; real options; absorptive capacity; Innovationsmanagement; Risikomanagement; Lernprozess; Realoption; Wissenstransfer; Theorie; Deutschland